Effect of annealing on the mechanical properties and the degradation of electrospun polydioxanone filaments. (March 2017) - Abhari, Roxanna E.; Mouthuy, Pierre-Alexis; Zargar, Nasim; Brown, Cameron; Carr, Andrew
Abstract: Annealing, or heat treatment, has traditionally been used as a treatment to improve the strength and stiffness of electrospun materials. Understanding the extent to which annealing can improve the mechanical properties and alter the degradation rate of electrospun polydioxanone filaments could influence the range of its potential clinical applications. In this study, we investigated the effect of annealing electrospun polydioxanone filaments at varying times and temperatures and subsequently subjecting them to in vitro degradation in phosphate buffer saline for up to 6 weeks. Fibre alignment, tensile strength and thermal properties were assessed. It was determined that annealing at 65 °C for 3 h only marginally improved the tensile strength (9±2%) but had a significant effect on reducing strain and rate of degradation, as well as maintaining fibre alignment within the filament. The filament retained significantly more of its force at failure after 4 weeks (82±15%, compared to 61±20% for non annealed filaments) and after 6 weeks of degradation (81±9%, compared to 55±13% for non annealed filaments). Conversely, annealing filaments at 75°C improved the initial tensile strength of the filament (17±6%), but over 6 weeks, both samples annealed at 75 °C and 85 °C otherwise performed similarly or mechanically worse than those not annealed. These findings suggest that annealing at low temperatures is more useful as a method to tailor degradation rate than to improve mechanical properties. The ability to modulate the degradation profile with annealing may become useful to tailor the properties of electrospun materials without altering the chemistry of the polymer used. This might better match the degradation of the implant and gradual loss of mechanical properties with the new matrix deposition within the structure, enabling multiple regenerative strategies within a single biomaterial system.